A study Of Some Geotechnical Properties of Quaternary Deposits in AL_Mahzam Area Salahadden and its Suitability For Concrete Using - Mohannad Issa khuder (Tikrit Journal of Pure Science)
The aim of this research is to studying some geotechnical properties of Quaternary deposits in AL-Mahzam area /Salahaddin governorate and evaluate  suitability of coarse soil for concrete samples have been collected from two stations using channel sampling and according to grain size analyses the type of soil is (GW-GP) according to unified soil classification and the values of specific gravity and absorption ratio ranges (2.61-6-08) (0.42-0.67)% respectively the chemical analysis for gypsum content , total dissolved salts, organic matters content and pH are (1.02-6.08) % (0.52- 11.03)% (0.52-0.81)% and (7.82-7.91)% respectively durability geotechnical test (loss Angeles) ranges between (14.4-15.1)% as a maximum limit allowed for the loss of weight for the cement concrete work (35%) depending on the American Standard [8] From these results we note that the study area models suitable for use in concrete works